(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The article employs a deductive method to analyze judicial activism in the cases of MI No. 4,733 and ADO No. 26, which highlighted the Brazilian Supreme Court’s (STF) intervention in response to the National Congress’s legislative inaction. In these rulings, the STF acted to address legislative inertia in criminalizing discriminatory practices — particularly those involving sexual orientation and gender identity — by expanding the scope of Law No. 7.716/1989 (which criminalizes racism). The STF’s actions in these cases marked a clear departure from the judiciary’s traditional role: rather than merely adjudicating constitutional issues within the confines of ongoing proceedings, the court went further by proposing normative solutions to fill gaps left by the Legislature. These interventions exemplify how the judiciary can assume an active role in safeguarding fundamental rights, overcoming legislative omissions. In analyzing the context of these decisions, this article focused on identifying the application of institutional dialogue theory, examining interactions between the Judiciary and Legislature as a mechanism to balance the protection of individual rights. It demonstrates that, even in adversarial interactions, the Judiciary can prompt the Legislature to act, fostering a continuous and necessary dialogue to codify fundamental rights and guarantees.